A Study of the Relationship of Academic Achievement and Impulsivity in Children with Specific Learning Disabilities to Parenting Strain and Sense of Competence in their Mothers - Usha Barahmand,; Faeze Piri,; Ali Khazaee, (Penerbit UKM, 2015)
The purpose of this research was to study the relationship of academic achievement and impulsivity in children with learning disorders with parenting strain and self-competence of their mothers. A sample of 70 students with learning disorders along with their mothers was recruited for the study. Data were collected using the UPPS Impulsive Behavior Scale, a modifi ed version of Zarit Burden Interview, Parent Sense of Competence Scale and each student’s grade point average as an index of academic achievement. Data were analyzed using Pearson’s correlation coeffi cients and multiple regression analysis. Findings revealed that academic achievement correlates signifi cantly and positively with mothers’ sense of competence but negatively with their experience of parenting strain. Furthermore, children’s impulsivity was negatively associated with mothers’ sense of competence but showed no relationship to parenting strain. Regression analysis indicated that while children’s impulsivity predicted mothers’ sense of competence but not their parenting strain, children’s academic achievement predicted both. Findings imply that when children with learning disorders are highly impulsive, their mothers only report an incapability to cope with stress. But when children’s academic achievement is low, mothers tend to not only experience increasing parenting stress but also report feeling overwhelmed by the stress. Findings imply that features of children with learning disorders have a differential impact on the mental health of their mothers.